PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN BUDAYA MUTU PENDIDIKAN TINGGI (STUDI KASUS STKOM AL MA’SOEM) - Tonton Taufik Rahman (Masoem University, 2019)
The Chairperson as the highest leader in STKOM Al Ma’soem plays an important role in building a quality culture. The quality culture is built through the establishment and implementation of a quality assurance system that is based on the National Higher Education Standards (SN-Dikti) and the Standards Beyond SN-Dikti. This study aims to answer how to build a quality culture of higher education through transformational leadership using SWOT analysis. This study uses a qualitative descriptive method, using SWOT analysis. School-based management applications carried out by a private education leader to improve the quality of education and realize the welfare of school citizens can be done by developing innovations in the aspects of entrepreneurship and providing education based on national education standards.